Ultrastructure and Biological Properties of Avian Infectious Bronchitis Virus Following Cryopreservation - Stegniy, Marina Yu.; Stegniy, Boris T.; Goltsev, Anatoliy N. (Problems of Cryobiology and Cryomedicine, 2015)
The authors investigated ultrastructure and infectious activity of avian infectious bronchitis virus following cryopreservation and low temperature storage at –20, –70 and –196°C during various terms from 3 days up to 8 years using electron microscopy, serologic and virusologic methods. It was shown that the lower was the storage temperature of cryopreserved viruses, the higher was the preservation of their ultrastructure and biological properties. Ultrastructure changes in IBV following long-term storage at moderate low temperatures (–20°C) included the damages of virion lipoprotein membrane, loss of glycoprotein ‘crown’ in most virions, conformation destabilization of membrane and nucleocapside. Following storage of IBV at –70 and –196°C the most virions retained electric charge and the ‘crown’ peplomers during whole observation term, damaged lipoproteid envelope and compromized structure were found only in 10% of total virions. Probl Cryobiol Cryomed 2015; 25(4):340-349.